The mediating role of postoperative blood glucose in the relationship between body composition and overall survival in non-diabetic gastric cancer patients - Ning Lan; Min Lai; Ying Gao; Xuan Wang; Min Chen; Shuheng Bai; Junyang Wang; Wenzhen Yuan; Juan Ren (BMC Cancer)
Abstract Background Postoperative hyperglycemia is common in gastric cancer (GC) patients, especially during enteral and parenteral nutrition. While the importance of postoperative glycemic control in diabetic patients is well-recognized, the management of blood glucose (BG) in non-diabetic patients after surgery has received less attention. This study aimed to investigate the impact of postoperative BG levels on overall survival (OS) in non-diabetic GC patients. Additionally, we explored whether postoperative BG mediates the relationship between body composition parameters and postoperative survival, and to what extent this mediation occurs. Methods A total of 349 patients who underwent curative surgery for GC in the Department of Oncology at The First Hospital of Lanzhou University from March 2017 to June 2021 were included in the study. Patients were stratified into groups based on postoperative BG levels, and differences in OS were analyzed. Univariate and multivariate Cox regression analyses were performed to identify independent factors influencing OS. Multivariate linear regression and correlation analyses were conducted to explore factors affecting postoperative blood glucose and its association with preoperative body composition parameters. A mediation analysis was conducted to assess the role of postoperative BG in mediating the effect of body composition on long-term survival, with the significance of the mediation effect tested using the bootstrap method. Results Age over 65, neoadjuvant chemotherapy, visceral adipose tissue index (VATI), surgical approach, pTNM stage, and postoperative hyperglycemia (HG) were identified as independent predictors of OS. Preoperative VATI, subcutaneous adipose tissue index, skeletal muscle density, random venous plasma glucose, hemoglobin, and total protein were significant factors influencing postoperative BG, and were significantly correlated with postoperative BG levels. Postoperative BG exhibited a significant negative mediating effect (-12.9%, 95%CI: -32.1% to -2.0%, p = 0.024) in the association between VATI and survival outcomes. Conclusion Both preoperative body composition and postoperative BG are important factors influencing OS in non-diabetic GC patients. The positive impact of VATI on OS is partially offset by the negative mediating effect of postoperative BG. Therefore, postoperative glycemic control in non-diabetic patients should receive sufficient attention, with proactive prevention and management strategies to improve patient outcomes.